2005
DOI: 10.1002/ana.20442
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic pathology of dopa‐responsive dystonia

Abstract: We used [(18)F]-fluorodeoxyglucose and positron emission tomography to determine a discrete cerebral pattern of abnormal glucose utilization in dopa-responsive dystonia. Network analysis demonstrated that dopa-responsive dystonia is associated with a specific pattern of regional metabolic covariation, characterized by increases in the dorsal midbrain, cerebellum, and supplementary motor area, as well as reductions in motor and lateral premotor cortex and in the basal ganglia. This pattern was not expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…We have found that this disease is associated with a specific spatial covariance pattern involving metabolic abnormalities in basal ganglia thalamocortical functional/anatomic pathways (Eidelberg et al, 1994(Eidelberg et al, , 1997. Indeed, this PD-related covariance pattern (PDRP) has been detected in multiple independent patient populations scanned in the resting condition (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…We have found that this disease is associated with a specific spatial covariance pattern involving metabolic abnormalities in basal ganglia thalamocortical functional/anatomic pathways (Eidelberg et al, 1994(Eidelberg et al, , 1997. Indeed, this PD-related covariance pattern (PDRP) has been detected in multiple independent patient populations scanned in the resting condition (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Using this network-modeling approach, we have found that PD patients express an abnormal metabolic pattern characterized by increased pallido-thalamic and pontine activity associated with relative reductions in cortical motor regions (Eidelberg et al, 1994(Eidelberg et al, , 1997cf., Carbon et al, 2003a). To date, this PD-related pattern (PDRP) has been detected in eight independent patient populations (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005;Eckert et al, in press) and its expression has been found to be highly reproducible in individual subjects (Ma et al, in press). In addition to accurately discriminating between PD patients and controls (Asanuma et al, 2005;Ma et al, in press), PDRP expression has been found to correlate consistently with Unified Parkinson's Disease Rating Scale (UPDRS) motor scores (Eidelberg et al, 1995;Lozza et al, 2004;Asanuma et al, 2006) and with clinical responses to therapy (e.g., Trošt et al, 2006;Asanuma et al, 2006;cf., Carbon et al, 2003a;Eckert and Eidelberg, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, network analyses of regional PET data have consistently revealed the presence of a reproducible abnormal spatial covariance pattern associated with parkinsonism (Eidelberg et al, 1994;Moeller et al, 1999;Lozza et al, 2004;Asanuma et al, 2005a). This PD-related pattern (PDRP) is characterized by pallido-thalamic and pontine hypermetabolism associated with relative metabolic decrements in premotor, prefrontal, and posterior parietal cortical regions (Carbon and Eidelberg, 2002;Asanuma et al, 2005a). We have attributed this abnormal metabolic topography to overactivity of internal pallidal (GPi) afferents from STN and consequent increases in inhibitory pallidal outflow to the ventral thalamus and pons (Eidelberg et al, 1994(Eidelberg et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%